Assessing a bundle of peer counseling, mobile phone messages, and mama kits in promoting timely initiation of and exclusive breastfeeding in Uganda: A cluster randomized controlled study. - David Mukunya; James K Tumwine; Grace Ndeezi; Milton W Musaba; Justin Bruno Tongun; Josephine Tumuhamye; Agnes Napyo; Faith Oguttu; Daphine Amanya; Beatrice Odongkara; Vincentina Achora; Thorkild Tylleskar; et al. (PLoS ONE, 2025)
Background Timely initiation of and exclusive breastfeeding have been recommended as key interventions to enable countries to attain the sustainable development target of reducing neonatal mortality to no more than 12 deaths per 1000 live births and to reduce mortality of children under 5 years to no more than 25 deaths per 1000 live births. Methods We conducted a cluster randomized controlled trial with the main objective to assess the effect of an integrated package consisting of: peer counseling, mobile phone messages, and mama kits on promoting health facility births between January 2018 and February 2019, in Lira district, Northern Uganda. In this article, we assessed the effect of the intervention on our two secondary objectives: timely initiation of and exclusivity of breastfeeding. We used a generalized estimation equation of the Poisson family, with a log or identity link, taking clustering into account to estimate prevalence ratios and prevalence differences. Results A total of 64% (594/926) of participants in the intervention arm initiated breastfeeding within the first hour after birth compared to 60% (493/829) in the control arm. The proportion of participants in the intervention arm that initiated breastfeeding within the first hour of life did not significantly differ from that in the control arm [Prevalence Ratio (PR) 1.08 (0.97 to 1.21)] and [Prevalence Difference (PD) 0.05 (-0.02 to 0.12)]. When we restricted the analysis to only mothers who decided on when to breastfeed, there was some evidence of intervention effectiveness [PR 1.20, 95% CI (0.99-1.5)]. In the intervention arm, 89% (804/904) of participants exclusively breastfed their infants in the first month of life compared to 81% (656/813) in the control arm. Participants in the intervention arm were 10% more likely to have exclusively breastfed in the preceding 24 hours compared to mothers in the control arm [PR 1.10 (1.04 to 1.17)] and [PD 0.08 (0.04 to 0.13)], and 16% more likely to have exclusively breastfed since birth compared to mothers in the control arm [PR 1.16 (1.03 to 1.30)] and [PD 0.12 (0.03 to 0.20]. Conclusion The intervention improved the proportion of mothers who practiced exclusive breastfeeding in the first month of life, but did not increase the proportion of mothers who initiated breastfeeding in the first hour of life. Future breastfeeding promotion interventions should consider including a health facility component and improving maternal autonomy to promote timely initiation of breastfeeding.